WHAT IS IN A SURNAME? AN ENQUIRY INTO THE UNAUTHORISED NAME CHANGES OF MARRIED WOMEN (The Pretoria Student Law Review, 2023)
In recent years there have been reports of the Department of HomeAffairs changing women’s surnames to that of their husbands upon theconclusion of a marriage without the married women’s consent. Thisconduct by the Department of Home Affairs officials infringes, as thisarticle will argue, not only on the affected women’s right to justadministrative action but also on the rights to equality and dignity and,in some instances, freedom of movement and universal suffrage. Thisarticle enquires into the possibility of taking the conduct of theDepartment of Home Affairs, which arguably amounts to administrativeaction, on judicial review seeking systemic relief. It will look at thesexist and patriarchal social norms relied upon to justify the conduct ofthe Department of Home Affairs and calls for intervening measures thatnot only result in broader social recognition but also effectivelydismantle the systems and frameworks of inequality that continue tomarginalise and subjugate women in the socially constructed genderhierarchy.